White Organic Light-Emitting Diodes Using Two Phosphorescence Materials in a Starburst Hole-Transporting Layer. (29th November 2011) - Inden, Tomoya; Hishida, Tomoya; Takahashi, Masayuki; Ohsumi, Masato; Ohtani, Naoki
Abstract : We fabricated two kinds of white organic light-emitting diodes (WOLEDs); one consisted of two emissive materials of red and blue, and the other of three emissive materials of red, green, and blue. The red and blue emissive materials were phosphorescent. We evaluated the thickness dependence of the CIE coordinate, the external quantum efficiency (EQE), and the luminance by changing the thicknesses of the Ir(btp)2acac and FIrpic layers. Samples consisting of three emissive materials revealed the best CIE coordinate and the best EQE in the same sample structure. On the other hand, the samples consisting of two emissive materials revealed the best CIE coordinate and the best EQE in different structures. The best CIE coordinate of (0.33, 0.36) was observed by changing the thicknesses of the stacked active layers. The best EQE was 9.73%, which was observed in the sample consisting of different thickness of stacked active layers.